PENGARUH CUSTOMER EXPERIENCE TERHADAP REVISIT INTENTION DI TAMAN WISATA ALAM GUNUNG TANGKUBAN PERAHU - Yuniawati, Yeni; Finardi, Ajeng Dewi Indriyani (Universitas Pendidikan Indonesia, 2016)
Natural Park of Tangkuban Perahu Mountain is a tourists destination in the boundary city of Subang and West Bandung which has a very beautiful natural atmosphere. The Tourists mostly come from West Java, Jabodetabek, outside West Java even another country outside Indonesia. Therefore the authors do a pre-study on tourists revisit intention of Tangkuban Perahu which produce that tourists revisit intention is low. Implementing the customer experience be expected could be increase the revisit intention to Tangkuban Perahu. This type of research is descriptive and verification, the survey method used is the systematic random sampling technique, with a sample size of 100 respondents. Data analysis technique using the multiple regression techniques. These results shows there is a partial influence customer experience consisting of comfort, education, hedonic, novelty, safety and beauty to tourists revisit intention of Tangkuban Perahu. The beauty dimension of customer experience variable got the highest score and the intention to recommend in revisit intention got the highest score.